Permeability Properties of Rickettsia mooseri - Myers, W. F. (1967)
The passive permeability properties of Rickettsia mooseri to both inorganic and organic solutes have been examined. Visual observations by phase-contrast microscopy of rickettsiae in macerated yolk sacs taken directly from heavily infected eggs revealed plasmolysis with hypertonic NaCl and KCl as well as with sucrose solutions. In contrast, similar visual studies of rickettsiae which had been subjected to freezing or to a purification process, or both, were plasmolyzed by hypertonic sucrose but not by hypertonic NaCl and KCl. These primary observations were extended to a variety of solutes and were placed on a quantitative basis by use of optical density and radioisotope dilution methods. Intracellular Na(+) and K(+) concentrations in processed rickettsiae, measured by flame photometry, closely paralleled the concentration of these ions in the suspending medium. It was concluded that R. mooseri appears to possess an osmotically active, functional, and structural membrane distinct from the cell wall, located at the surface of a structure analogous to the bacterial protoplast. In the intact organism, this membrane is passively impermeable to sucrose, NaCl, and KCl. However, altered permeability properties, especially to inorganic electrolytes, may be expected in rickettsiae which have been stored in the frozen state and subjected to a lengthy purification process.